2014
DOI: 10.1186/1471-2229-14-115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the response to eleven Colletotrichum lindemuthianum races in a RIL population of common bean (Phaseolus vulgaris L.)

Abstract: BackgroundBean anthracnose is caused by the fungus Colletotrichum lindemuthianum (Sacc. & Magnus) Lams.- Scrib. Resistance to C. lindemuthianum in common bean (Phaseolus vulgaris L.) generally follows a qualitative mode of inheritance. The pathogen shows extensive pathogenic variation and up to 20 anthracnose resistance loci (named Co-), conferring resistance to specific races, have been described. Anthracnose resistance has generally been investigated by analyzing a limited number of isolates or races in segr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 42 publications
(60 reference statements)
6
78
0
1
Order By: Relevance
“…Isolates 14835 and 14834 were pathogenic to six; isolates 14789, 14788, 14652, and 14782 were pathogenic to five; and the other isolates, 14779, 14783, 14781, 14784, 1467, and 14780, were pathogenic in four cultivars or fewer (Figure 1). The interaction between P. vulgaris and C. lindemuthianum was studied by Campa, Rodríguez-Suárez, Giraldez, and Ferreira (2014), and the authors reported that this interaction is specific and complex, conditioned by the pathogenic variation and by the genotype. They identified by mapping the RIL's population 'Cornell49242 x Xana' two resistance genes for race 65, which exhibited a dominance action mode unlike the other races, which exhibited different action modes in both parents and might be eventually addictive or dominant.…”
Section: Resultsmentioning
confidence: 99%
“…Isolates 14835 and 14834 were pathogenic to six; isolates 14789, 14788, 14652, and 14782 were pathogenic to five; and the other isolates, 14779, 14783, 14781, 14784, 1467, and 14780, were pathogenic in four cultivars or fewer (Figure 1). The interaction between P. vulgaris and C. lindemuthianum was studied by Campa, Rodríguez-Suárez, Giraldez, and Ferreira (2014), and the authors reported that this interaction is specific and complex, conditioned by the pathogenic variation and by the genotype. They identified by mapping the RIL's population 'Cornell49242 x Xana' two resistance genes for race 65, which exhibited a dominance action mode unlike the other races, which exhibited different action modes in both parents and might be eventually addictive or dominant.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, twenty-three related anthracnose resistance genes have been identified by the ‘ Co ’ symbol, including Co-1 to Co-7 , Co-8 , Co-9 to Co-15 , Co-17 , Co-u to Co-z , and CoPv09 [35]. Among these genes, Co-1 , Co-x and Co-w belong to the Andean gene pool, and the others belong to the Mesoamerican gene pool.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Co-5 , Co-6 and Co-v were located on the Pv07 [18,19], Co-4 on the Pv08 linkage group and Co-2 on the Pv11 [16,20,21]. Recently, Campa et al identified a new gene CoPv09 on Pv09 [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Seventeen independent loci, Co-1 to Co-17 , conditioning resistance have been mapped to eight bean chromosomes (Pv01, Pv02, Pv03, Pv04, Pv07, Pv08, Pv09 and Pv11) [11, 21, 22, 23], and a graphic depiction of the mapped Co genes is displayed in Meziadi et al [24]. Anthracnose resistance is dominant at all loci except the Co-8 locus, and multiple alleles have been identified at the Co-1 , Co-3 , Co-4 , and Co-5 loci.…”
Section: Introductionmentioning
confidence: 99%